Development of an acid-base e-module based on discovery learning and integrated with interactive learning media to improve chemistry literacy - Novalina Panja Putri Panjaitan; Andromeda Andromeda; Alizar Alizar; Okta Suryani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Low levels of students’ chemical literacy indicate the need for innovative learning resources, particularly for abstract and quantitative topics such as acid–base chemistry. This study aimed to develop and evaluate a Discovery Learning-based acid–base e-module integrated with interactive learning media. This Educational Design Research employed the Four-D (4-D) model. The study involved 16 students and four chemistry teachers in the needs analysis, six expert validators, two chemistry teachers and 30 students in practicality testing, and 26 Grade XII students in effectiveness testing. Chemical literacy was measured using a 15-item test with excellent internal consistency (Cronbach’s α = 0.95). Data were analyzed using Aiken’s V, percentage scores, N-gain, Shapiro–Wilk, and paired-samples t-test. The e-module obtained an Aiken’s V of 0.83, indicating validity, while practicality scores were 94.44% for teachers and 91.20% for students, with a combined score of 92.82%, categorized as very practical. The mean chemical literacy score increased from 5.42 to 61.14, with an N-gain of 0.59, categorized as moderate. The paired-samples t-test showed a significant difference between pretest and posttest scores, t(25) = 20.00, p < .001. The developed e-module is therefore a valid and highly practical learning resource that provides preliminary evidence of its potential to improve students’ chemical literacy in acid–base chemistry.